DocuEase: Document Management System for MZR Global Sdn. Bhd. - MOHD KAMEEL, ALEEZ NATASHA; KASIM, SHAHREEN (Applied Information Technology And Computer Science, 2025)
DocuEase, a web-based document management system, was developed to address MZR Global Sdn Bhd’s manual filing inefficiencies and security vulnerabilities. The system resolves challenges including data loss, disorganized documents, and time-consuming approval processes. Developed using Agile methodology with Laravel framework, DocuEase features role-based access control, automated approval workflows, secure document storage, and comprehensive audit logging. User Acceptance Testing with 24 participants showed satisfaction rates of 91.3% to 100% across evaluation criteria. The implementation successfully transformed manual processes into an efficient, secure digital solution, improving productivity and reducing administrative workloads.